2004
DOI: 10.1091/mbc.e03-06-0427
|View full text |Cite|
|
Sign up to set email alerts
|

The eps8 Family of Proteins Links Growth Factor Stimulation to Actin Reorganization Generating Functional Redundancy in the Ras/Rac Pathway

Abstract: Sos-1, a guanine nucleotide exchange factor (GEF), eps8 and Abi1, two signaling proteins, and the lipid kinase phosphoinositide 3-kinase (PI3-K), assemble in a multimolecular complex required for Rac activation leading to actin cytoskeletal remodeling. Consistently, eps8 ؊/؊ fibroblasts fail to form membrane ruffles in response to growth factor stimulation. Surprisingly, eps8 null mice are healthy, fertile, and display no overt phenotype, suggesting the existence of functional redundancy within this pathway. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 27 publications
5
111
0
Order By: Relevance
“…S2). The distribution of Eps8L2 overlapped with that of Eps8 (15,16) as previously suggested in other systems (17). However, the spatiotemporal expression patterns in cochlear hair cells were different.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…S2). The distribution of Eps8L2 overlapped with that of Eps8 (15,16) as previously suggested in other systems (17). However, the spatiotemporal expression patterns in cochlear hair cells were different.…”
Section: Resultssupporting
confidence: 82%
“…Eps8L2 is structurally the most closely related to Eps8 and shares very similar expression patterns, suggesting some level of redundancy in most tissues (17). We have shown that Eps8L2 is expressed at the apical ends of hair cells and at the tips of mechanosensory stereocilia in mammalian inner ear hair cells.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations